Toward Real-Time Determination of Yield Coefficients of Early-Stage Electroactive Biofilms by Optical Microscopy - Scarabotti, Francesco; Kuchenbuch, Anne; Kallies, René; Bühler, Katja; Harnisch, Falk (Frontiers in Energy Research, 2022)
Physiological cellular parameters, such as latency times (lagt), cell production rates (CPR), doubling times (td), relative growth rates (RGR), and yield coefficients (YNe), are only known as endpoint measurements for electroactive microorganisms (EAM). Here we show that these can be gained non-invasively and in real-time for early-stage biofilm formation at electrodes using a microfluidic electrochemical flow-cell (EFC) allowing in vivo optical microscopy. Parameters obtained for early-stage mixed culture biofilm anodes formed at +150 mV vs. Ag/AgCl sat. KCl have lagt of 2.31–4.58 days, CPR of 0.72–1.20 × 105 cells h−1, td of 176.54–1838.65 min, RGR of 0.02–0.27 h−1, and YNe of 5.99–7.94 × 1012 cells mole-−1. However, oxygen permeation into the EFC was the main problem that remained unsolved during the study that provides interesting lessons for future improvements.